Critical Dialogues of Urban Governance, Development and Activism London and Toronto - Bunce, Susannah; Livingstone, Nicola; March, Loren; Moore, Susan; Walks, Alan (UCL Press, 2020)
Cities have been sites of some of the most visible manifestations of the evolution of processes of globalization and population expansion, and global cities are at the cutting edge of such changes. Critical Dialogues of Urban Governance, Development and Activism examines changes in governance, property development, urban politics and community activism, in two key global cities: London and Toronto. The analysis is inherently comparative, but not in the traditional sense - the volume does not seek to deliver a like-for-like comparison. Instead, taking these two cities as empirical cases, the chapters engage in constructive dialogues about the contested and variegated built forms, formal and informal governmental mechanisms and practices, and policy and community-based responses to contemporary urban concerns. The authors position a critical dialogue on three central issues in contemporary urban studies: governance, real estate and housing, and community activism and engagement. Their less traditional approach to comparative framing seeks to understand London and Toronto from a nuanced perspective, promoting critical reflection on the experiences and evaluative critiques of each urban context, providing insight into each city's urban trajectory and engaging critically with wider phenomena and influences on the urban governance challenges beyond these two cities.